Ring Oscillators with Additional Phase Detectors as a Random Source in a Random Number Generator - Łukasz Matuszewski; Mieczysław Jessa; Jakub Nikonowicz (Entropy)
In this paper, we propose a method to enhance the performance of a random number generator (RNG) that exploits ring oscillators (ROs). Our approach employs additional phase detectors to extract more entropy; thus, RNG uses fewer resources to produce bit sequences that pass all statistical tests proposed by National Institute of Standards and Technology (NIST). Generating a specified number of bits is on-demand, eliminating the need for continuous RNG operation. This feature enhances the security of the produced sequences, as eavesdroppers are unable to observe the continuous random bit generation process, such as through monitoring power lines. Furthermore, our research demonstrates that the proposed RNG’s perfect properties remain unaffected by the manufacturer of the field-programmable gate arrays (FPGAs) used for implementation. This independence ensures the RNG’s reliability and consistency across various FPGA manufacturers. Additionally, we highlight that the tests recommended by the NIST may prove insufficient in assessing the randomness of the output bit streams produced by RO-based RNGs.